Pengaruh Religiusitas dan Jiwa Sosial terhadap Keputusan Donasi Online pada Generasi Zilenial di Kota Mojokerto: Perspektif Ekonomi Syariah di Era Digital - Rahayu, Ira; Rahma Sandhi Prahara (STEI Kanjeng Sepuh Gresik Jawa Timur, 2025)
The zillennial generation is the generation most closely connected to the internet. This digital lifestyle has become an integral part of most Indonesians' lives. Nearly half of people's time, especially in large urban areas, is spent using digital devices, whether for education, work, comThis study aims to identify the influence of religiosity and social spirit on online donation decisions among the Ziennial generation in Mojokerto City. The method used is quantitative with a survey approach, and data were collected through questionnaires from 100 respondents selected using a non-probability sampling method with the Slovin formula calculation. Data analysis was carried out using multiple linear regression. The results showed that religiosity has a positive and significant effect on online donation decisions, with a calculated t value of 4.963 which is greater than the t table of 1.980. Similarly, the social spirit variable also has a positive and significant effect, with a calculated t value of 3.368 which is greater than the t table of 1.980.munication, entertainment, or even charity work.Simultaneous tests show that religiosity and social spirit together have a significant influence on online donation decisions, as evidenced by the calculated F value of 3.793, greater than the F table of 3.09, with a significance level of 0.00 (less than 0.05). Thus, hypotheses H1, H2, and H3 are accepted, while H0 is rejected. This study shows that both religiosity and social spirit play an important role in influencing online donation decisions in the Ziennial generation, which provides insight into psychological and social factors in digital donation behavior.